SYNTHESIS AND CHARACTERIZATION OF 7-HYDROXYCOUMARIN CONTAINING NEW TYPE OF PHTHALOCYANINE COMPOUNDS AND INVESTIGATION OF THERMAL AND ELECTROCHEMICAL PROPERTIES - DAUDA, AMINU (Fırat Üniveristesi, 2017)
Hem sübstitüentlerin pozisyonu hem de koordinasyon için kullanılan metalin türü ile ftalosiyaninlerin farklı özelliklerini belirlemek ve sentezlemek için, periferal olmayan pozisyonlarda 7-hidroksikumarin taşıyan tetrasübstitüe nikel, cobalt, çinko, bakır, krom ve demir-ftalosiyaninler, 1,3-diiminoizoindolin ile sentezlenen ftalosiyanin türevinin siklotetramerizasyon reaksiyonundan sentezlendi. Yeni bileşiklerin yapıları 1H NMR, 13C NMR, UV-Vis ve FT-IR spektroskopi yöntemleri kullanılarak karakterize edildi. DMF'de Nikel, cobalt, çinko, bakır, krom ve demir-ftalosiyanin bileşiklerinin (NiPc, CoPc, ZnPc, CuPc, FePc, CrPc) elektronik spektrumları verilmiştir. DMF içerisinde ZnPc, CuPc, FePc ve CrPc'nin UV-Vis spektrumlarında Q bandları 690 nm de gözlendi. CoPc ve FePc komplekslerinin Q bandları ise sırasıyla 677 ve 678 nm de gözlendi. Ftalosiyanin türevlerinin termal kararlılıkları TGA ile kontrol edildi. Bozunma sıcaklıklarını belirlemek için ftalosiyanin kompleksleri 700 0C'ye kadar ısıtıldı. NiPc, CoPc, ZnPc, CrPc, CuPc ve FePc bileşiklerinin bozunmaya başladıkları sıcaklıklar sırasıyla 309, 300, 306, 350, 354 ve 380 0C dir. CoPc, ZnPc ve FePc az çözünmesine karşılık, NiPc'nin DMF'deki çözünürlüğü elektrokimyasal çalışma için yeterli olduğu bulunmuştur. Metalli ftalosiyaninlerin düşük çözünürlüğü periferal sübstitüe ftalosiyaninlerin deneylerinin kapsamı ile sınırlıdır. Bu nedenle bu çalışmada hazırlanan metalli ftalosiyaninlerin yüksek sıcaklıklarda termal olarak kararlı olduğunu ve farklı uygulamalarda kullanılabilme potansiyeline sahip olduğu söylenebilir.

To synthesized and evaluate the variation of the properties of phthalocyanines with both the position of the substituents and the type of metal used for coordination, tetrasubstituted nickel, cobalt, zinc, copper, chromium and Iron, phthalocyanines bearing 7-hydroxycoumarin as substituents were synthesized by the cyclotetramerization reaction of the synthesized phthalonitrile derivatives and 1,3-diiminoisoindoline. The structures of the synthesized compounds were characterized by a combination of 1H NMR, 13C NMR, UV-Vis, and FT-IR spectrophotometry. The electronic spectra of nickel, cobalt, zinc, copper, ıron, chromium phthalocyanine compounds (NiPc, CoPc, ZnPc, CuPc, FePc, CrPc) in DMF are given. The UV-Vis absorption spectra of ZnPc, CuPc, NiPc, and CrPc, in DMF, showed intense Q absorption at 690nm. The Q band absorptions were also observed at 677 nm and 678 nm, respectively, for CoPc, and FePc. The thermal stability of the phthalocyanine derivatives were checked by TGA and then the phthalocyanines were heated up to 700 oC to determine their degradation temperature. The temperatures at which the phthalocyanine began to exhibit weight loss were 309, 300, 306, 350, 354 and 380 oC for NiPc, CoPc, ZnPc, CrPc, CuPc, and FePc respectively. For electrochemical work in DMF, NiPc was found to be sufficiently soluble whereas CoPc, ZnPc, and FePc were poorly soluble. The low solubility of the metal phthalocyanines limited the scope of experiments of the peripherally substituted phthalocyanines. It could, therefore, be concluded that the metal phthalocyanines prepared in this study showed suitably high thermal stability and can be used for various applications.
Yeni tip ftalosiyanin bileşikleri içeren 7-hidroksikumarinin sentezi ve karakterizasyonu ve termal ve elektrokimyasal özelliklerin incelenmesi
Keywords: Kimya